Bentuk-bentuk Kreativitas Guru Bimbingan dan Konseling dalam Pelayanan Bimbingan dan Konseling pada Masa Pandemi Covid 19 di SMP Negeri 2 Bukittinggi - Ardila, Meisy; Rahmi, Alfi (TSAQOFAH, 2023)
This research is motivated by the problems faced by counseling teachers that students do not participate in the learning process. In general, in carrying out the learning process, teachers should be able to apply various learning methods and strategies that can develop students' potential and are also able to stimulate the growth and development of student creativity. In fostering students' creativity, counseling teachers/counselors can provide services to students according to student needs. The purpose of this study was to identify and describe the Forms of Creativity of Guidance and Counseling Teachers in Guidance and Counseling Services during the Covid 19 Pandemic at SMP N 2 Bukittinggi.This research is a qualitative research with a descriptive approach. The key informant I is the counseling teacher and the supporting informant is V students at SMP N 2 Bukittinggi. Data was collected through observation and interviews. Data analysis techniques use data reduction, data display, data conclusion and verification. Data validation techniques by comparing the results of key informant interviews with supporting informants and comparing what was said in general and privately. The results of this study conclude that the form of creativity that has been carried out by the counseling teacher at SMP N 2 Bukittinggi, namely: 1) The counseling teacher has been creative in providing counseling services to students, 2) During this pandemic the counseling teacher used e counseling in the learning process to make it easier students in participating in the learning process, 3) Providing counseling services using email to students, namely online counseling rooms, 4) Providing counseling services using chat to students such as via WhatsApp, 5) Providing counseling services using video conferencing to students such as zoom meetings, 6) Students very enthusiastic in participating in counseling services using e counseling.